2006
DOI: 10.2135/cropsci2005.06-0102
|View full text |Cite
|
Sign up to set email alerts
|

Reaction to Three Races of Fusarium Wilt in the Phaseolus vulgaris Core Collection

Abstract: Seven races of Fusarium oxysporum f. sp. phaseoli Kendrick and Snyder (Fop) cause Fusarium wilt (FW) disease of common bean (Phaseolus vulgaris L.). FW occurs worldwide and has recently become a serious disease in the central and western USA. The objectives of this research were to identify new sources of resistance to Fop, characterize the Central/South American (CA/SA) Phaseolus Core Collection for reaction to races 1, 4, and 5 Fop and determine if a previously reported sequence characterized amplified regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
3
12
0
1
Order By: Relevance
“…Regions located in linkage group B2 and B5 were associated with root rot resistance; however, neither of these linkage groups were associated with root rot resistance in the present study. The lack of agreement of the results of the present study with previous studies (Fall et al, 2001; Román‐Avilés and Kelly, 2005; Brick et al, 2006) may be partially due to their focus on Fusarium wilt and Fusarium root rot and supports previous reports that Fusarium spp. do not play a significant role in the root rot complex evaluated at Hancock, WI (Boomstra, 1975; Beebe and Bliss, 1979).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Regions located in linkage group B2 and B5 were associated with root rot resistance; however, neither of these linkage groups were associated with root rot resistance in the present study. The lack of agreement of the results of the present study with previous studies (Fall et al, 2001; Román‐Avilés and Kelly, 2005; Brick et al, 2006) may be partially due to their focus on Fusarium wilt and Fusarium root rot and supports previous reports that Fusarium spp. do not play a significant role in the root rot complex evaluated at Hancock, WI (Boomstra, 1975; Beebe and Bliss, 1979).…”
Section: Resultssupporting
confidence: 83%
“…Fall (2001) also developed a sequence characterized amplified region (SCAR) marker to facilitate the large scale use of the linkage relationship between U20.750 and resistance to Fusarium wilt. Brick et al (2006) evaluated the SCAR marker developed by Fall (2001) to determine its usefulness to characterize resistance to Fusarium wilt in 202 accessions that represented the USDA Central and South American P. vulgaris core collection. Results indicated that amplification of the SCAR marker developed by Fall (2001) was not associated with resistance to F. oxysporum f. sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of core collections in these neglected crops provides researchers opportunity to discover new sources of variation for use in genetic improvement of these crops. To date, research at ICRISAT and elsewhere has proven beyond doubt the utility of these representative subsets in identifying agronomically beneficial germplasm for use in crop breeding (Bowman et al, 2001;Brick et al, 2006;Grunwald et al, 2003;Mahuku et al, 2003;Micklas et al, 1999;Tullu et al, 2001;Upadhyaya et al, 2013Upadhyaya et al, , 2014. Molecular characterization of these subsets should further provide information on population structure and diversity and allelic richness, which may be used to identify genetically diverse germplasm for use in genomics and applied breeding of these crops.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have accessed diversity in the CIAT collection (Tohme et al 1996;Beebe et al 2000Beebe et al , 2001Blair et al 2006;Diaz and Blair 2006). Fewer studies of the diversity in the NPGS have been performed (Miklas et al 1999;Brick et al 2006).…”
Section: Introductionmentioning
confidence: 99%